Fixation of chronic suture exostosis in a mature horse. (20th November 2013) - Klein, L.; Sacks, M.; Fürst, A. E.; Del Chicca, F.; Grest, P.; Jackson, M. A.
Summary This case report describes the clinical findings, diagnosis and treatment of a 14‐year‐old Warmblood gelding with suture exostosis. The horse was referred to our clinic because of bilateral swelling in the region of the frontal and nasal bone junction and bilateral epiphora. Epiphora was the main concern for the owner and the reason for further investigation and treatment. Radiographic examination showed extensive bone proliferation on the dorsal frontal and nasal bones. Computed tomographic (CT) images further characterised the periosteal proliferation as new bone formation and localised it along the frontonasal and frontolacrimal suture lines. Computed tomographic images also showed pathological changes of both lacrimal ducts. A chronic fracture was suspected to be the cause of the periosteal proliferation, and surgical treatment using 2 small 2.4 Unilock plates was chosen to stabilise the suture between the frontal and nasal bones. The swelling decreased and the epiphora resolved by 6 months post operatively. A CT examination 2 years later showed complete healing.